Ineffective health self-management in chronic conditions: a systematic review - Dantas, Ana Clara; Araújo, Jéssica Naiara de Medeiros; Lopes, Marcos Venícios de Oliveira; Borges, Bárbara Ebilizarda Coutinho; Silva, Cyntia Leenara Bezerra da; Medeiros, Hanna Priscilla da Silva; Silva, Amanda Barbosa da; Vitor, Allyne Fortes (Acta paulista de enfermagem, 2025)
Abstract Objective To analyze clinical indicators related to the nursing diagnosis Ineffective health self-management in people with chronic conditions. Methods A systematic review of diagnostic accuracy, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and prepared according to the JBI Manual for Evidence Synthesis recommendations. The last access date in data sources was May 27, 2024. The definition of clinical indicators was performed by analyzing the observable clues/inferences that represented manifestations of the phenomenon of interest to nursing, with an inductive and data-based approach. Results In the 22 selected studies, the following clinical indicators were found: failure to include treatment regimen into daily living (36.3%), sedentary lifestyle (31.8%), smoking (27.2%), excessive alcohol consumption (22.7%), impaired glucose regulation (18.1%), failure to take action that reduces risk factors (13.6%), failure to attend appointments with health care provider (13.6%), ineffective choices in daily living for meeting health goal (13.6%), insufficient self-monitoring of health patterns (13.6%), ineffective stress management (13.6%), sleep pattern disturbance (4.5%), insufficient liquid intake (4.5%), difficulty adhering to diet (4.5%), inattentive to disease symptoms (4.5%), and exacerbation of disease symptoms (4.5%). Conclusion This review allowed the analysis of 15 clinical indicators relevant to nursing care for people with chronic conditions who present ineffective self-management of their health, of which nine are not present in the NANDA International classification. Resumo Objetivo Analisar os indicadores clínicos relacionados ao diagnóstico de enfermagem autogestão ineficaz da saúde em pessoas com condições crônicas. Métodos Revisão sistemática de acurácia diagnóstica, guiada pelo Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) e elaborada conforme as recomendações do JBI Manual for Evidence Synthesis. A última data de acesso nas fontes de dados foi em 27 de maio de 2024. A definição dos indicadores clínicos foi realizada por análise das pistas/inferências observáveis que representassem manifestações do fenômeno de interesse da enfermagem, com abordagem indutiva e baseada nos dados. Resultados Nos 22 estudos selecionados, os seguintes indicadores clínicos foram constatados: falha na inclusão do regime de tratamento na vida diária (36,3%), estilo de vida sedentário (31,8%), tabagismo (27,2%), consumo excessivo de álcool (22,7%), regulação da glicose prejudicada (18,1%), falha na ação para reduzir os fatores de risco (13,6%), falha em comparecer a compromissos agendados com profissional da saúde (13,6%), escolhas ineficazes na vida diária para o cumprimento das metas de saúde (13,6%), automonitoramento dos padrões de saúde insuficiente (13,6%), gerenciamento do estresse ineficaz (13,6%), distúrbio no padrão de sono (4,5%), ingestão de água insuficiente (4,5%), dificuldade de adesão à dieta (4,5%), desatenção aos sintomas da doença (4,5%) e exacerbação dos sintomas da doença (4,5%). Conclusão Essa revisão permitiu a análise de 15 indicadores clínicos relevantes para a assistência de enfermagem a pessoas com condições crônicas que apresentam autogestão ineficaz da saúde, dos quais 9 não estão presentes na classificação da NANDA Internacional. Resumen Objetivo Analizar los indicadores clínicos relacionados con el diagnóstico de enfermería “autogestión ineficaz de la salud en personas con afecciones crónicas”. Métodos Revisión sistemática de precisión diagnóstica, guiada por el Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) y elaborada de acuerdo con las recomendaciones del JBI Manual for Evidence Synthesis. La última fecha de acceso a las fuentes de datos fue el 27 de mayo de 2024. La definición de los indicadores clínicos fue realizada por el análisis de las pistas/inferencias observables que representaban manifestaciones del fenómeno de interés de enfermería, con un enfoque inductivo y basado en los datos. Resultados En los 22 estudios seleccionados, se observaron los siguientes indicadores clínicos: fracaso al incluir el régimen terapéutico en la vida diaria (36,3 %), estilo de vida sedentaria (31,8 %), tabaquismo (27,2 %), consumo excesivo de alcohol (22,7 %), regulación de la glucosa perjudicada (18,1 %), fracaso al emprender acciones para reducir los factores de riesgo (13,6 %), fracaso en acudir a las citas con el proveedor de salud (13,6 %), decisiones ineficaces en la vida diaria para alcanzar los objetivos de salud (13,6 %), autovigilancia de los estándares de salud insuficiente (13,6 %), manejo ineficaz del estrés (13,6 %), trastorno de los patrones de sueño (4,5 %), ingesta de agua insuficiente (4,5 %), dificultad para cumplir la dieta (4,5 %), falta de atención a los síntomas de la enfermedad (4,5 %) y exacerbación de los síntomas de la enfermedad (4,5 %). Conclusión Esta revisión permitió el análisis de 15 indicadores clínicos relevantes para la atención de enfermería a personas con afecciones crónicas que presentan una autogestión ineficaz de la salud, de los cuales nueve no están presentes en la clasificación NANDA Internacional.